History and modernity: multimodality and interactivity of museums’ communication (based on coronation 2023 exhibitions at british museums) - Biliuk , Julia (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article explores multimodality and interactivity at British museums exhibitions on occasion of the King Charles III and Queen Camilla coronation May 6, 2023. The research can be considered a significant contribution to museum studies, particularly in the realm of visitor engagement and education. Drawing on a multimodal discourse analysis framework, the study examines how museums utilise a combination of semiotic resources, such as visual, textual, audio, sensory as well as digital elements, to engage visitors both onsite and online. This analysis highlights museums as dynamic communicative spaces that challenge traditional discourse models by integrating interactivity, participation, and educational engagement, thereby reshaping how cultural heritage is presented and experienced. Through a detailed examination of five key exhibitions, Coronation Robes at Apsley House, Crown to Couture at Kensington Palace, Royal Connections: Crowns and Coronets at Blenheim Palace, the Coronation Display at Buckingham Palace, and the exhibition at the Royal Mews, the research demonstrates how multimodal strategies facilitate meaning-making, educational enrichment, and visitor engagement. The research offers valuable insights into museology, highlighting how digitalisation is transforming the way museums operate in today’s world. The use of digital tools, social media platforms, and interactive displays is shown to enhance the accessibility and inclusivity of museum discourse, democratising the visitor experience. In particular, the concept of the participatory museum is explored, where visitors are encouraged to actively engage and contribute to the museum experience rather than passively consume it. The data includes photographic documentation collected by the researcher (https://drive.google.com/ drive/folders/1oTXxklKfv53HBJzpXrLAqvtTC6ZQe_N3?usp=share_link), illustrating the integration of multimodal resources within the exhibitions. The study contributes to the growing body of research on multimodality, interactivity, and education in museum communication, offering insights into how these strategies reshape visitor interaction with cultural heritage. The findings suggest further inquiry into the role of multimodal discourse in enhancing visitor comprehension, engagement, and learning, particularly within the context of evolving digital museum practices.